A new species of Yunnanilus (Cypriniformes: Nemacheilidae) from Sichuan, southwest China - Du, Li-Na; Hou, Mian; Chen, Xiao-Yong; Yang, Jun-Xing (Zootaxa, 2018)
A new species of Yunnanilus is described from Tuojiang River, Sichuan, China. The new species, Yunnanilus jiuchiensis, can be distinguished from other species of Yunnanilus by the following combination of characters: processus dentiformis absent; body covered with scarce scales; lateral-line incomplete, as long as half the length of the pectoral-fin length, with 6–11 pores; eye diameter larger than interorbital width; and caudal-peduncle length less than its depth.